PREVALENCIA DE BRUCELOSIS CANINA EN DOS DISTRITOS DE LA PROVINCIA CONSTITUCIONAL DEL CALLAO - Ramírez L., Hernán (2006)
The objective of this study was to determine the prevalence of canine brucellosis(Brucella canis) in two districts of the province of Callao. A total of 456 sera werecollected from dogs without distinction of breed, sex and age. Samples were analyzed bythe Agar Gel Immunodiffusion (AGID) test using B. ovis antigen. The results indicatedthat 15.6 ± 3.3 (71/456) of sampled animals were positive. No statistical differences werefound due to district, breed, sex or age; however, differences were found (p<0.05) beetweendogs with and without reproductive history (26.5 and 8.6% respectively).